A simple, fast, and sensitive colorimetric assay for visual detection of berberine in human plasma by NaHSO4-optimized gold nanoparticles. Issue 55 (11th July 2017) - Hu, Ziwei; Xie, Mingshan; Yang, Danting; Chen, Dong; Jian, Jingyi; Li, Haibin; Yuan, Kaisong; Jiang, Zhengjin; Zhou, Haibo
Abstract : Herein, we report a simple, fast and sensitive colorimetric visualization of berberine in human plasma using NaHSO4 -optimized gold nanoparticles. The LOD in human plasma is 0.24 μg mL −1 by the naked eye and 0.06 μg mL −1 by UV-vis spectroscopy. Abstract : Berberine is an important anti-inflammatory drug widely used for the treatment of heart and intestinal disorders. The quantification of berberine is usually required in clinic medical assays. Herein, we report simple, fast and sensitive colorimetric visualization of berberine in human plasma using citrate-stabilized gold nanoparticles (AuNPs). Upon exposure to μg mL −1 levels of berberine, the AuNP solution exhibits a highly sensitive color change from red to blue and rapid aggregation kinetics within the initial 10 min, which can be directly seen with the naked eye and monitored by UV-vis absorbance spectroscopy. As confirmed by comparison with potential coexisting foreign substances, the presence of positively charged berberine induces the aggregation of the AuNPs owing to the electrostatic attraction and coordination interactions between the ring nitrogen atoms of berberine and the AuNPs, causing a color change of the AuNP suspension. Further evidence is that the sensitivity is significantly improved when NaHSO4 is added to promote the ligand exchange between citrate and berberine at the surface of the AuNPs. The NaHSO4 -optimized AuNP system provides a simple colorimetric assay for the rapid detection of berberine in human plasma. The limit of detection (LOD) is 0.24 μg mL −1 by the naked eye and 0.06 μg mL −1 by UV-vis spectroscopy.